2021
DOI: 10.3390/plants10122596
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Early White Quality Protein Maize Inbreds and Derived Hybrids under Low-Nitrogen and Combined Drought and Heat Stress Environments

Abstract: An increase in the average global temperature and drought is anticipated in sub-Saharan Africa (SSA) as a result of climate change. Therefore, early white quality protein maize (QPM) hybrids with tolerance to combined drought and heat stress (CDHS) as well as low soil nitrogen (low-nitrogen) have the potential to mitigate the adverse effects of climate change. Ninety-six early QPM hybrids and four checks were evaluated in Nigeria for two years under CDHS, low-nitrogen, and in optimal environments. The objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…These results provide a basis for rapid genetic gains from selection and identification of hybrids with desirable traits for each research condition [22,23]. Significant environment mean squares observed for anthesis-silking interval and husk cover under managed drought indicated that the difference in environmental conditions that prevailed in the two years of evaluation affected these trait [24]. A similar trend of results was observed for grain yield, anthesis-silking interval, plant aspect, and ears per plant under well-watered conditions.…”
Section: Discussionsupporting
confidence: 58%
“…These results provide a basis for rapid genetic gains from selection and identification of hybrids with desirable traits for each research condition [22,23]. Significant environment mean squares observed for anthesis-silking interval and husk cover under managed drought indicated that the difference in environmental conditions that prevailed in the two years of evaluation affected these trait [24]. A similar trend of results was observed for grain yield, anthesis-silking interval, plant aspect, and ears per plant under well-watered conditions.…”
Section: Discussionsupporting
confidence: 58%
“…Maize is an important staple crop for about half of the human population in sub-Saharan Africa (SSA). Due to its economic importance, it is anticipated to become the most important cereal crop by 2025 across the world (FAOSTAT, 2017;Bhadmus et al, 2021). However, factors such as drought and low soil N severely hamper its productivity and production across the sub-region, thereby increasing food and nutritional insecurity (Badu-Apraku et al, 2011;Annor and Badu-Apraku, 2016;Kountche et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, the levels of lysine and tryptophan are inadequate. This makes children fed on non-quality protein maize (non-QPM) without other dietary protein sources suffer growth deformities such as kwashiorkor due to malnutrition (Olakojo et al, 2007;Upadhyay et al, 2009;Mbuya et al, 2011;Annor et al, 2019;Bhadmus et al, 2021). Quality protein maize, however, can provide 73% of the protein needs of human beings and contains nearly twice the quantity of tryptophan and lysine in the non-QPM endosperm (Annor et al, 2019;Bhadmus et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Over 4.5 billion people in developing countries obtain ~ 30% of their calories from maize. In sub-Saharan Africa (SSA), maize is the most widely grown and consumed staple food with an estimated 50% of the populace depending on maize as the primary staple [ 1 , 2 ]. Maize ranks first in the world cereal production (1.15 billion tons) with the United States of America as the largest producer (~ 50% of the total production) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%